Hypertensionand Comorbidities: Exploring Interconnections and Advances in Management - Dhoke, Sanat Mahendra; Prajapati, Mishthi; Varghese, Syno Mariam; Pillai, Anmol; Magar, Meensher Thapa; Nayak , SP Srinivas (Asian Journal of Pharmaceutical Research and Development, 2025)
Hypertension (HTN) is a major worldwide health concern, frequently exacerbated by its close links to chronic illnesses like diabetes and asthma. The complex interactions between hypertension and associated comorbidities are examined in this review, with a focus on common pathophysiological processes such as oxidative stress, systemic inflammation, and dysregulated renin-angiotensin-aldosterone system (RAAS) activation. The risk of cardiovascular and renal problems is greatly increased when these linkages are present, especially in those who have diabetes and asthma. In order to lower morbidity and mortality in hypertensive individuals with diabetes, it is vital to achieve strict blood pressure management, as evidenced by large-scale studies like the HOT and ABCD trials. The management of hypertension is further complicated by inflammatory endotypes linked to asthma, which calls for specialised treatment strategies.Significant progress has been made in personalised medicine with recent developments in the treatment of hypertension, such as the use of mineralocorticoid receptor antagonists, endothelin receptor blockers, and novel chronotherapy. These tactics seek to minimise side effects while optimising blood pressure regulation. However, safety issues and the need for more study to confirm these medicines’ long-term effectiveness pose challenges to their application. In order to enhance outcomes and lessen the worldwide burden of disease linked to hypertension, this review emphasises the use of specific medicine in the management of hypertension and its comorbidities and promotes a patient-centric approach.